Struggle as Metaphor in European Union Discourses on Unemployment - STRAEHLE, CAROLYN and WEISS, GILBERT and WODAK, RUTH and MUNTIGL, PETER and SEDLAK, MARIA (Discourse & Society, 1999)
This study looks at how, over a period of several years, unemployment in two genres (speeches and Presidency Conclusions) generated in organizations of the European Union (EU) is constructed both as a `problem' and a `fight' and how these formulations can be viewed as closely connected under an overarching metaphor of `struggle'. A synthesis of discourse analytic and cognitive-semantic analyses, this article begins by demonstrating how struggle is invoked and then proceeds to decompose the notion into several categories, using statistical analysis to show their distribution. Ultimately, it is demonstrated that the differences between the two genres are connected to their respective purposes and target audiences, with Presidency Conclusions examples of internal organizational discourse and commissioners' speeches as external organizational discourse. The similarities between the two genres reflect the functions of the struggle metaphor in EU discourses of unemployment in general, the ways in which its dimensions serve various legitimizing functions in these genres' capacity as political discourse, and the connection between discourses on unemployment and the prevailing EU economic philosophy.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTk5MDEwMDAxMDA0